KEBIJAKAN HUKUM DALAM PENANGGULANGAN TINDAK PIDANA YANG TERJADI PADA WARGA BINAAN DI LEMBAGA MASYARAKAT - Heri Edrino Sihombing; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2023)
The correctional system is organized in the context of forming Correctional Families to become fully human beings, aware of mistakes, improve themselves and not repeat criminal acts so that they can be accepted again by society. The problems are the factors that cause criminal acts against inmates in the Medan Class I Penitentiary, and law enforcement efforts in tackling the occurrence of crimes that occur in inmates in the Medan Class I Penitentiary, as well as the obstacles faced by the Medan Class I Penitentiary in carrying out coaching for correctional inmates which has implications for the occurrence of criminal acts, the research method is normative juridical supported by empirical data. The results of his research are the factors that cause crime because of room capacity, economic inequality that causes social inequality, the number of wardens that are not proportional to the number of prisoners, there is no courtesy among fellow prisoners. Legal efforts carried out by the Medan Class I Lapas in dealing with crime use penal and non penal efforts, the obstacles faced by the Medan Class I Lapas are limited coaching facilities, and the factor of prison space capacity, as well as the level of education